Determination of the depth of irrigational soil layer for apple [Malus pumila] tree on dwarfing rootstock - Kato, T. (Aomori-ken. Apple Experiment Station, Kuroishi (Japan)) (Transactions of The Japanese Society of Irrigation, Drainage and Reclamation Engineering, 1992)
Apple tree on dwarfing rootstock is shallow-rooted compared with that on Malus prunifolia rootstock and stands more in need of irrigation because of its main root system region distributed in the surface layer having violent moisture variation. However, since the conventional apple tree on Malus prunifolia rootstock has not suffered from drought so frequently, the actual state is that it is not fully being secured with irrigation water. Then, with the view of establishing proper water management technique allowing for water saving, I examined the relationship of the depth of irrigational soil layer with the growth, yield and fruit quality of apple tree on dwarfing rootstock. According to the depth of irrigational soil layer, 4 plots of treatment were set up, i. e. plot of effective soil layer (80cm), plot of main root zone (30cm), plot of 2/3 (20cm) of the latter and plot of 1/3 (10cm) of the latter, with the volume and frequency of irrigation being minimal for the third plot. The fourth plot having shallow irrigational soil layer showed a greater irrigation frequency than the other plots and a more irrigation volume than the third plot, which is approximate to that for the second plot. The tree growth volume and the tree size tended to be greater for deeper irrigational soil layer, but no significant inter-plot difference was noted in the yield and fruit growth, and the fruit quality was best for the third plot. The above results suggest that the depth of irrigational soil layer for apple tree on dwarfing rootstock is preferably of the order of the 2/3 of the important soil layer for growth rather than the current effective soil layer because of highly possible production of good quality fruits, lesser irrigation volume and effective availability of rainfall.